BERFIKIR SECARA TRANSPARAN DAN ARGUMENTASI (Berfungsi untuk menganalisis dan menjelaskan pentingnya berfikir secara Transparan dan logis terhadap berbagai aspek komunikasi Bisnis) - Suradi, Endang (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
In  a  typical days  at  work or  college we are  likely to be confronted   with arguments coming in all shapes and sizes.                                                   - Reading the newspaper over brealifast or listening to the morning news. We will come under the influence of other persons or organisations trying to convince us of the correctness of their views on everything from the best value cereal to eat to who we should votefor in the next election.At college, we will be expected to criticallyjudge  the value of what we read in books and articles, and be able to produce essays and reports which are logical and well-organised.At work, we will have reports to read (and write) in which it will be extremely important dto judge  whether the conclusions and recommendations reached are correct or not.As we advance in our careers, this skill of clear thinking becomes ever more important as quick  and accurate judgments  have to be made on many other peoples  arguments  and submissions. So important  is it to  think  clearly in relation to our own and others ideas that it is difficult to imagine a successful person who does not have this ability.The purpose of this chapter is to introduce the main types of argument used in everyday life, with a view not only to being able to convincingly demonstrate- to ourselves and our  "opponents"» the reasonsfor such a judgment. Most people have a rough, instinctive idea of the value of argument, but lack the ability to put forward the exact the reasons why the argument is good or bad.